State Civil Apparatus Welfare of Public Elementary School Teachers in Bandar Lampung City - Ulul Azmi; Ida Budiarty (Maneggio, 2024)
Teacher welfare is an important aspect that affects the standard, quality of life, and work of teachers. The components of welfare for the Indonesian State Civil Servant (ASN) are basic salary, allowances, work environment, security aspects in granting civil servant (PNS) status, awards, work-life balance between working hours and workload, and the development of certified teacher professionalism. The study population was ASN SDN teachers totaling 1466 people. Sampling using purposional sampling random method based on the lottery obtained a sample size of 155 people. The research objective was to determine the effect of consumption expenditure, education level, training, work experience, and teacher certification on the welfare of ASN SDN teachers in Bandar Lampung City. The estimation method used Ordinary Least Square (OLS). The findings are that the level of education, training, work experience, and teacher certification have a positive and significant effect on the welfare of ASN primary school teachers in Bandar Lampung City, while consumption expenditure has a negative and significant effect on the welfare of ASN primary school teachers in Bandar Lampung City. In the future, it is necessary to improve education, training, and experience, as well as teacher certification to improve welfare. In addition, it is necessary to maintain the purchasing power of teachers' income so that it is not eroded by inflation which reduces purchasing power.